Role of Pop-Up Advertising and Sales Promotion on Customer Purchasing Decisions with Customer Satisfaction as a Mediating Variable - Allfio Justin Zebaja Ristiand; Abdi, Antonius Surjo (Jurnal Manajemen Bisnis, 2024)
This research will contribute valuable insight into the role of pop-up advertising and sales promotions on customer purchasing decisions, with customer satisfaction as a mediating variable. The population of this study is the Indonesian population who are able and accustomed to using the Internet. This research uses a probability sampling method. The research method used by researchers is simple random sampling, namely members of a certain population, namely some Indonesian citizens who can use the internet and are familiar with pop-up advertisements and sales promotions, will be used as samples. The results of the research show that pop-up advertising has a direct and positive effect on customer satisfaction, sales promotions have a direct and positive effect on customer satisfaction, and show that pop-up advertising does not have a direct and positive effect on customer purchasing decisions. Sales promotion initiatives have a direct and beneficial effect. in increasing the overall level of customer satisfaction.